Effects of wall curvature and streamwise pressure gradient on film cooling effectiveness. (25th August 2016) - Qin, Yanmin; Chen, Pingting; Ren, Jing; Jiang, Hongde
Highlights: Film cooling with streamwise pressure gradient on curved walls was investigated. The effects of wall curvature are opposite for high or low momentum ratios. The critical momentum ratio increases with an increase in favorable pressure gradient. Effects of streamwise pressure gradient and wall curvature should not be neglected. Abstract: As the load of a modern turbine is increasing, the turning angle and the flow acceleration is increasing. The effects of streamwise pressure gradient (SPG) and wall curvature on film cooling performance are becoming more and more important. Film cooling effectiveness with those two effects was investigated experimentally and numerically. Flow on the concave wall has an unstable effect and increases the turbulence intensity which leads to a faster dissipation and wider lateral spreading. With these two opposite effects, there is a critical point that when the momentum ratio is smaller than the certain value, film cooling effectiveness is highest on concave wall and the rank is opposite when the momentum ratio is larger than the value. The critical momentum ratio is 0.6 with nonaccelerated main flow for all density ratios. For the cases with different SPG, the critical momentum ratio still exists, while the value increases with stronger favorable pressure gradient and ranges from 0.55 to 0.75 in the present research. The film cooling performance with different SPG and wall curvature is quite different from the flat wall case and thus these effects should be taken into consideration in gas turbine film cooling design.